Kajian Peningkatan Implementasi Sistem Akuntabilitas Kinerja Instansi Pemerintah Melalui Pembangunan Aplikasi Evaluasi Akuntabilitas Kinerja Instansi Pemerintah - Abdi Pradana, Achmad Arfiandys; Maghfiroh, Lutfi Rahmatuti (Politeknik Statistika STIS, 2024)
Inspektorat Utama Statistic Indonesia (BPS) is a division that responsible for carrying out evaluations of Accountability Performance for Government Agency (AKIP). Currently the system used in the evaluation still utilizes several third party applications which have limitations. Apart from that, in the Evaluation Result Report (LHE) BPS Republic of Indonesia there is a recommendation that BPS have an independent application. Therefore, Inspektorat Utama needs to conduct a study on improving the implementation of the performance accountability system for government agencies through developing an application that can meet these needs. Application development begins with collecting data for needs analysis which is followed by application design, design implementation as well as evaluation and testing. The application was built using the System Development Life Cycle method, iterative waterfall model. The applications that have been built are evaluated using the Computer System Usability Questionnaire and tested using black box testing. The application testing results show that all functions work properly, while the evaluation results show that users are very satisfied with the performance and appearance of the application.